2005
DOI: 10.1093/ndt/gfh672
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone resorption in HD patients: is it caused by elevated RANKL synthesis?

Abstract: Serum RANKL levels were significantly higher in HD patients than in healthy age-matched controls. Moreover, RANKL levels were significantly higher in the upper PTH tertile, indicating enhanced RANKL synthesis in a PTH-dependent fashion. Thus, our clinical findings clearly support published in vitro studies that demonstrated a stimulating effect of PTH on RANKL synthesis. Therefore, the hypothesis that PTH increases bone resorption in HD patients through RANKL appears valid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 15 publications
6
13
1
Order By: Relevance
“…It has been assumed that the 'proinflammatory' profile of cytokines observed in atherosclerosis increases the RANKL/OPG ratio and in this way causes accumulation of calcium deposits [17]. Our in vitro findings seem to confirm numerous reports on the presence of inverse relationship between the concentration of OPG and RANKL also in vessels that are free of calcification [18].…”
Section: Discussionsupporting
confidence: 89%
“…It has been assumed that the 'proinflammatory' profile of cytokines observed in atherosclerosis increases the RANKL/OPG ratio and in this way causes accumulation of calcium deposits [17]. Our in vitro findings seem to confirm numerous reports on the presence of inverse relationship between the concentration of OPG and RANKL also in vessels that are free of calcification [18].…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, an in vivo study showed an increased level of circulating bone-specific AlkPhos in patients with CKD in the presence of aortic calcification (45). Even though active vitamin D analogs including calcitriol may directly modulate calcifying processes leading to decreased vascular calcification, their salutary affects may also be mediated via osteopontin and AlkPhos pathways (6).…”
Section: Discussionmentioning
confidence: 99%
“…Avbersek-Luznik et al study showed that serum OPG levels were 6,4-fold higher in dialysis patients compared to controls, and was depended on PTH concentration [38]. Another research by Avbersek-Luznik et al support hypothesis that PTH increases bone resorbtion in HD patients through stimulating RANKL synthesis [40]. Conversely, in Doumouchtsis study, the average serum concentration of sRANKL was lower in patients on HD than in age-matched healthy controls [36] .…”
Section: Opg/rank/rankl System In Esrdmentioning
confidence: 93%
“…OPG concentrations are reported to be higher in HD patients [35][36][37][38][39], whereas RANKL level can be higher [39,40], lower [36] or within normal range [41] compared to healthy individuals. Kazama showed that serum OPG levels in uremic patients were elevated and independent of their serum PTH levels, what suggested the circulating OPG to be an independent factor affecting bone metabolism in uremic patients [42].…”
Section: Opg/rank/rankl System In Esrdmentioning
confidence: 99%